La société chinoise après Mao : entre autorité et modernité. - Auberl, Claude; Chevrier, Yves; Domenach, Jean-Luc; Hua, C.-M.; Lew, Roland; Zafanolli, W. (Paris : Fayard, 1986)
Bibliotheek François Vercammen
Frans
Monografie